Kinetics of Oxidation of Galactose and Mannose with Iodine in Alkaline Media - Singh, M.K.; Prasad, N.; Sinha, H.K. (Asian Journal of Chemistry, 2012)
The kinetics of oxidation of galactose and mannose with iodine in alkaline media have been investigated at different pH. The results indicate that the active oxidizing species is hypoiodous acid. The maximum oxidation in each case is found around pH 11.20. A first order dependence in hypoiodous acid, in galactose and in mannose has been observed. Change in ionic strength of the medium shows no effect on the reaction rate. A probable mechanism consistent with experimental results has been proposed.